Postiridotomy Ultrasound Biomicroscopy Features in the Fellow Eye of Chinese Patients with Acute Primary Angle-Closure and Chronic Primary Angle-Closure Glaucoma. Issue 3 (March 2015) - Chen, Hui-Jin; Wang, Xin; Yan, Yu-Jie; Wu, Ling-Ling
Abstract : Purpose: To compare the features of postiridotomy ultrasound biomicroscopy (UBM) in Chinese patients with acute primary angle-closure (aPAC) and with chronic primary angle-closure (cPAC) glaucoma. Patients and Methods: Consecutive cases were classified into acute and chronic groups. The acute group included 77 patients with unilateral aPAC. The chronic group included 57 patients with unilateral advanced cPAC glaucoma. In both the groups, the patients' fellow eye underwent a laser iridotomy and was studied. The main outcome measures included qualitative UBM parameters such as a plateau iris, anterior iris insertion, and an anteriorly rotated ciliary process and quantitative UBM parameters such as central anterior chamber depth (ACD), basal iris thickness (IT500), and scleral ciliary process angle (SCPA). Results: For the qualitative parameters, more eyes in the chronic group had a plateau iris ( P =0.046), an anterior iris insertion ( P =0.222), and an anteriorly rotated ciliary process ( P =0.090) than those in the acute group. For the quantitative parameters, the eyes in the chronic group had a deeper ACD ( P <0.001), thicker IT500 ( P <0.001), and smaller SCPA ( P <0.001) than those in the acute group. Conclusions: The UBM features of Chinese patients with cPAC include a more plateaued iris, a thicker basal iris, and a smaller SCPA, whereas patients with aPAC may have a shallower ACD. For Chinese patients, a nonpupillary block component may play a more important role in asymptomatic cPAC than in aPAC.